Experimentally fitted biodynamic models for pedestrian–structure interaction in walking situations. (May 2016) - Toso, Marcelo André; Gomes, Herbert Martins; da Silva, Felipe Tavares; Pimentel, Roberto Leal
Abstract: The interaction between moving humans and structures usually occurs in slender structures in which the level of vibration is potentially high. Furthermore, there is the addition of mass to the structural system due to the presence of people and an increase in damping due to the human body´s ability to absorb vibrational energy. In this paper, a test campaign is presented to obtain parameters for a single degree of freedom (SDOF) biodynamic model that represents the action of a walking pedestrian in the vertical direction. The parameters of this model are the mass ( m ), damping ( c ) and stiffness ( k ). The measurements were performed on a force platform, and the inputs were the spectral acceleration amplitudes of the first three harmonics at the waist level of the test subjects and the corresponding amplitudes of the first three harmonics of the vertical ground reaction force. This leads to a system of nonlinear equations that is solved using a gradient-based optimization algorithm. A set of individuals took part in the tests to ensure inter-subject variability, and, regression expressions and an artificial neural network (ANN) were used to relate the biodynamic parameters to the pacing rate and the body mass of the pedestrians. The results showed some scatter in damping and stiffness that could not be precisely correlated with the masses and pacing rates of the subjects. The use of the ANN resulted in significant improvements in the parameter expressions with a low uncertainty. Finally, the measured vertical accelerations on a prototype footbridge show the adequacy of the numerical model for the representation of the effects of walking pedestrians on a structure. The results are consistent for many crowd densities. Highlights: It is presented a test campaign on pedestrians to fit a SDOF biodynamic model. Measurements are performed on a force platform considering several individuals. Regression functions and neural networks are used to relate biodynamic parameters. Accelerations are measured on a prototype footbridge crossed by pedestrians. The numerical model results are in agreement with the experimental measurements.